2011
DOI: 10.1183/09031936.00111811
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise training in patients with COPD: the role of muscle fatigue

Abstract: The improvement in exercise performance in response to exercise training varies greatly from one patient with chronic obstructive pulmonary disease to another. It is possible that in a portion of patients the muscle stimulus applied during exercise training is insufficient to elicit training effects. We investigated whether patients presenting quadriceps contractile fatigue after training have more favourable effects of a rehabilitation programme.46 patients followed a 3-month high-intensity exercise training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
85
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 39 publications
0
85
0
2
Order By: Relevance
“…The corollary of this is, therefore, that ''non-fatiguers'' should benefit less from rehabilitation than ''fatiguers''. This is, however, not completely true, because it has recently been shown that exercise tolerance has improved after rehabilitation even in ''non-fatiguers'' [75]. The picture is very complex, and may involve several other contributing factors such as exertional dyspnoea, ventilatory limitation/constraint, dynamic lung hyperinflation and lack of motivation.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The corollary of this is, therefore, that ''non-fatiguers'' should benefit less from rehabilitation than ''fatiguers''. This is, however, not completely true, because it has recently been shown that exercise tolerance has improved after rehabilitation even in ''non-fatiguers'' [75]. The picture is very complex, and may involve several other contributing factors such as exertional dyspnoea, ventilatory limitation/constraint, dynamic lung hyperinflation and lack of motivation.…”
mentioning
confidence: 87%
“…For example, high intensity or longer duration programmes have been associated with a larger response compared with less intense or shorter programmes [73,74]. Patients who present with significant contractile fatigue after an exercise training session also show more pronounced training effects [75]. Some COPD patients with pronounced muscle wasting (cachectic patients) seem to be more prone to the effect of oxidative stress and inflammation at the muscle level [51,62,63,76].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these studies highlight the potential contribution of the distal limb muscle fatigue in daily physical activities in patients with COPD. The occurrence of muscle fatigue may also modulate the response to exercise training programs, as illustrated by the observation that patients with COPD developing quadriceps fatigue during exercise training have larger training effects compared with those who did not fatigue during the same session (299).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Firstly, one of the main reasons for using NLPE training, according to Klijn and colleagues, is the possibility of avoiding overtraining and, consequently, the development of muscle fatigue, optimizing the gains in muscle endurance and strength. However, Burtin and colleagues [18] recently suggested that developing fatigue during exercise training was associated with better outcomes in patients with COPD. Then, the role of muscle fatigue in the rehabilitation of patients with COPD still has to be elucidated.…”
mentioning
confidence: 99%